Positional demands of professional rugby - Lindsay, A.; Draper, N.; Lewis, J.; Gieseg, S. P. (European Journal of Sport Science, 2015)
Rugby union is a physically intense intermittent sport coupled with high force collisions. Each position within a team has specific requirements which are typically based on speed, size and skill. The aim of this study was to investigate the contemporary demands of each position and whether they can explain changes in psychophysiological stress. Urine and saliva samples were collected before and after five selected Super 15 rugby games from 37 players. Total neopterin (NP), cortisol and immunoglobulin A were analysed by SCX-high performance liquid chromatography and enzyme linked immunosorbent assay. Global positioning system software provided distance data, while live video analysis provided impact data. All contemporary demands were analysed as events per minute of game time. Forwards were involved in more total impacts, tackles and rucks compared to backs (p < 0.001), while backs were involved in more ball carries and covered more total distance and distance at high speed per minute of game time (p < 0.01). Loose forwards, inside and outside backs covered significantly more distance at high speed (p < 0.01), while there was a negligible difference with number of impacts between the forward positions. There was also minimal difference between positions in the percentage change in NP, cortisol and sIgA. The results indicate distance covered and number of impacts per minute of game time is position-dependent whereas changes in psychophysiological stress are independent. This information can be used to adapt training and recovery interventions to better prepare each position based on the physical requirements of the game.